2015
DOI: 10.15414/jmbfs.2015.4.5.434-436
|View full text |Cite
|
Sign up to set email alerts
|

ANTIMICROBIAL EVALUATION OF SESQUITERPENE Α-Curcumene AND ITS SYNERGISM WITH IMIPENEM

Abstract: α-Curcumene was isolated from the fresh aerial parts of Senecio selloi Spreng. DC. and its activity against bacteria, yeasts and an alga was inspected by the applying the microdilution method. The strongest effect was manifested against Saccharomyces cerevisiae with estimated values of MIC and MFC 0.8 mg/mL. The α-curcumene synergism in the concentrations of 1 mM and 5 mM, respectively, with selected antibiotics (ciprofloxacin, imipenem, ceftazidim and a combination of amoxicillin and clavulanic acid) was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Which means it may attenuate Parkinson's disease (Balakrishnan et al, 2018). The compound α-curcumene, have antimicrobial activity, Pozzatti et al (2015) concluded that fungal strains are more sensitive for α-curcumene than the bacterial ones. Elemicin inhibited the bacterial growth of NCTC 11168 strain (Rossi et al, 2007).…”
Section: Essential Oils (Eo) Yieldmentioning
confidence: 99%
“…Which means it may attenuate Parkinson's disease (Balakrishnan et al, 2018). The compound α-curcumene, have antimicrobial activity, Pozzatti et al (2015) concluded that fungal strains are more sensitive for α-curcumene than the bacterial ones. Elemicin inhibited the bacterial growth of NCTC 11168 strain (Rossi et al, 2007).…”
Section: Essential Oils (Eo) Yieldmentioning
confidence: 99%
“…Noticed mechanisms were inhibition of DNA replication as well as blocking of cellular respiration. Phytochemicals like choline ( Siopa et al, 2016 ), rhein ( Joung et al, 2012 ), limonene ( Vuuren and Viljoen, 2007 ), α-curcumene ( Santos da Silva et al, 2015 ), geraniol ( Lira et al, 2020 ), linalool ( Park S.-N. et al, 2012 ), camphor ( Masry et al, 2021 ), myrcene ( Chaves-Quirós et al, 2020 ), and α-pinene ( Dhar et al, 2014 ; Cloeckaert et al, 2015 ) which were earlier reported from Alternanthera pungens Kunth, may be responsible for such antimicrobial action.…”
Section: Introductionmentioning
confidence: 99%
“…Major compounds like zingerone, 6-gingerol, 8-shogaol, 6-shogaol, nortrachelogenin, isocaryophyllene, β-elemene, carinol, trans-nerolidol, α-curcumene, α-zingiberene, β-curcumene might be responsible for the antibacterial activity of this plant, as the antibacterial activity of these compounds have already been reported [14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%